Optimization of Mesa Etch for a Quasi-Vertical GaN Schottky Barrier Diode (SBD) by Inductively Coupled Plasma (ICP) and Device Characteristics - Yue Sun; Xuanwu Kang; Yingkui Zheng; Ke Wei; Pengfei Li; Wenbo Wang; Xinyu Liu; Guoqi Zhang (Nanomaterials, 2020)
The optimization of mesa etch for a quasi-vertical gallium nitride (GaN) Schottky barrier diode (SBD) by inductively coupled plasma (ICP) etching was comprehensively investigated in this work, including selection of the etching mask, ICP power, radio frequency (RF) power, ratio of mixed gas, flow rate, and chamber pressure, etc. In particular, the microtrench at the bottom corner of the mesa sidewall was eliminated by a combination of ICP dry etching and tetramethylammonium hydroxide (TMAH) wet treatment. Finally, a highly anisotropic profile of the mesa sidewall was realized by using the optimized etch recipe, and a quasi-vertical GaN SBD was demonstrated, achieving a low reverse current density of 10−8 A/cm2 at −10 V.